Association of IRF5 polymorphisms with activation of the interferon α pathway. Issue 3 (23rd October 2009) - Rullo, Ornella J; Woo, Jennifer M P; Wu, Hui; Hoftman, Alice D C; Maranian, Paul; Brahn, Brittany A; McCurdy, Deborah; Cantor, Rita M; Tsao, Betty P
Abstract : Objective: The genetic association of interferon regulatory factor 5 ( IRF5 ) with systemic lupus erythematosus (SLE) susceptibility has been convincingly established. To gain understanding of the effect of IRF5 variation in individuals without SLE, a study was undertaken to examine whether such genetic variation predisposes to activation of the interferon α (IFNα) pathway. Methods: Using a computer simulated approach, 14 single nucleotide polymorphisms (SNPs) and haplotypes of IRF5 were tested for association with mRNA expression levels of IRF5, IFNα and IFN-inducible genes and chemokines in lymphoblastoid cell lines (LCLs) from individuals of European (CEU), Han Chinese (CHB), Japanese (JPT) and Yoruba Nigerian (YRI) backgrounds. IFN-inducible gene expression was assessed in LCLs from children with SLE in the presence and absence of IFNα stimulation. Results: The major alleles of IRF5 rs13242262 and rs2280714 were associated with increased IRF5 mRNA expression levels in the CEU, CHB+JPT and YRI samples. The minor allele of IRF5 rs10488631 was associated with increased IRF5, IFNα and IFN-inducible chemokine expression in CEU (pc =0.0005, 0.01 and 0.04, respectively). A haplotype containing these risk alleles of rs13242262, rs10488631 and rs2280714 was associated with increased IRF5, IFNα and IFN-inducible chemokine expression in CEU LCLs. In vitro studies showed specific activation of IFN-inducible genes in LCLs by IFNα. Conclusions: SNPs of IRF5 in healthy individuals of a number of ethnic groups were associated with increased mRNA expression of IRF5. In European-derived individuals, an IRF5 haplotype was associated with increased IRF5, IFNα and IFN-inducible chemokine expression. Identifying individuals genetically predisposed to increased IFN-inducible gene and chemokine expression may allow early detection of risk for SLE.